The column shafts of the propylaia and stoa in the sanctuary of Athena at Lindos - Pakkanen, Jari (Proceedings of the Danish Institute at Athens, 1998)
In this study it is demonstrated that the column shaft of the late third century BC Stoa in the sanctuary of Athena Lindia had a slight entasis. The mid third century BC Propylaia probably had higher columns than E. Dyggve has suggested; the height of the larger facade order is most likely ca. 4.9 m and the smaller courtyard order ca. 4.6 m, both ca. 0.3 m higher than Dyggve’s suggestions. The study is based on the published measurements of the preserved column drums and the results are achieved by applying a method which combines computerised analysis with statistics. The new Propylaia column height is also supported by proportional comparison. The appendix of comparative material at the end of the paper presents previously unpublished dimensions on entasis in Hellenistic Doric buildings: in general the entasis proportions in Late Classical and Hellenistic buildings seem quite similar.